Characterization of BisI Homologs - Xu, Shuang-yong; Zemlyanskaya, Elena V.; Gonchar, Danila A.; Sun, Zhiyi; Weigele, Peter; Fomenkov, Alexey; Degtyarev, Sergey Kh; Roberts, Richard J. (Frontiers in Microbiology, 2021)
BisI is a sequence-specific and 5-methylcytosine (m5C)-dependent restriction endonuclease (REase), that cleaves the modified DNA sequence Gm5CNGC (G indicates that the cytosine opposite to G is modified). We expressed and purified a number of BisI homologs from sequenced bacterial genomes and used Illumina sequencing to determine the Pam7902I (Esp638I-like) cleavage sites in phage Xp12 DNA. One BisI homolog KpnW2I is EcoBLMcrX-like, cleaving GCNGC/RCNGY/RCNRC sites with m5C. We also cloned and expressed three BisI homologs from metagenome sequences derived from thermophilic sources. One enzyme EsaTMI is active at 37oC to 65oC. EsaHLI cleaves GCNGC sites with three to four m5C and is active up to 50oC. In addition, we determined the number and position of m5C in BisI sites for efficient cleavage. BisI cleavage efficiency of GCNGC site is as following: Gm5CNGC (two internal m5C) > Gm5CNGC (one internal m5C) > GCNGm5C (one external m5C) >>GCNGC (unmodified). Three or four m5C in GCNGC site also supports BisI cleavage although partial inhibition was observed on duplex oligos with four m5C. BisI can be used to partially cleave a desired GCNGC site targeted with a complementary oligonucleotide (hemi-methylated). The m5C-dependent BisI variants will be useful for epigenetic research.